Traditional uses, pharmacology, toxicology and chemical constituents of an aphrodisiac plant, Smilax myosotiflora: a systematic review - Rosdi, Rasmaizatul Akma; Sul’ain, Mohd Dasuki; Darnis, Deny Susanti; Wan Ishak, Wan Rosli (Hacettepe University, 2022)
Smilax myosotiflora is one of the well-known plants in Malaysian folk medicines for its aphrodisiac effect. The leaves and fruits were also claimed able to treat syphilis and rheumatism. This article aims to systematically provide an overview on the traditional uses, pharmacology, toxicology, and chemical constituents of S. myosotiflora. The e-searching on previous literature of the plant was conducted from its inception to the end 2021 according to the study’s criteria. The develop- ment of this review was based on the Cochrane Collaboration framework and PRISMA guidelines. As the result, it was found that over half of 41 eligible ar- ticles have discussed on its aphrodisiac attribution while others reported on the synergistic, sex reversal, antioxidant, anthelmintic activities and so forth. Two stilbenoid compounds are successfully isolated from the plant; trans-resveratrol and trans-3,3’,5,5’-tetrahydroxy-4’-methoxystilbene. Other than the detection of aurones and phytosterols, S. myosotiflora was delineated to be high in alkaloids, saponins and flavonoids. This systematic review can be a platform for other re- searchers to explore more on S. myosotiflora as it still has more pharmacology potential to be discovered. Further studies are required prior to the development of S. myosotiflora-based drugs for medicinal usage in the future.